Analysis of Students' Creative Thinking Ability with Problems Solving in Terms of Adversity Quotient - Muslim, Buchori; Suryaningsih, Siti; Aprianti, Rizqa Fadhila (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractStudents’ difficulties in chemistry subject are the main cause of their low rate to think creatively. Students with high adversity quotient are most likely to overcome the difficulties in finding a solution to answer the creative thinking problems. The objective of this research is to analyze the creative thinking ability in chemistry from the perspective of adversity quotient. The subjects of the study are 72 senior high school students from XII grade in Tangerang. The sampling applies a random sampling technique. Data collection technique is carried out by giving a test about chemical creative thinking skills in the form is essay question with 0,727 realibility scale. Adversity quotient data is obtained using a questionnaire scale with 0,652 realibility scale. The method used in this study is a descriptive qualitative and quantitative method. The result indicates that camper and quitter subjects are classified as creative and climber subjects are classified as very creative. The different aspects of students’ ability in solving problems can be used in mapping students' creative thinking abilities. As a recommendation, to improve creative thinking ability requires a high level of adversity quotient. Therefore, in this research students are expected to explore their creative thinking abilities in the learning process.AbstrakKesulitan siswa pada mata pelajaran kimia menjadikan rendahnya kemampuan berpikir kreatif. Siswa yang memiliki adversity quotient tinggi maka dapat mengatasi kesulitan untuk menemukan solusi jawaban dari soal berpikir kreatif. Tujuan dari penelitian adalah untuk menganalisis kemampuan berpikir kraetif kimia ditinjau dari adversity quotient. Subjek penelitian adalah siswa kelas XII SMA di Kabupaten Tangerang yang  sebanyak 72 orang. Pengambilan sampel menggunakan teknik random sampling. Teknik pengumpulan data dilakukan dengan melaksanakan tes kemampuan berpikir kreatif kimia berupa soal uraian dengan realibilitas sebesar 0,727. Data adversity quotient, diperoleh dengan menggunakan skala angket dengan realibilitas sebesar 0,652. Metode yang digunakan adalah metode deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa subjek camper dan quitter tergolong kreatif dan Subjek dengan climber tergolong sangat kreatif. Perbedaan aspek kemampuan siswa dalam mengatasi kesulitan dapat digunakan dalam memetakan kemampuan berpikir kreatif siswa. Sebagai rekomendasi, dengan memiliki tingkat adversity quotient yang tinggi dapat meningkatkan kemampuan berpikir kreatifnya. Oleh karena itu, Penelitian ini diharapkan siswa dapat mengeksplorasi kemampuan berpikir kreatifnya dalam proses pembelajaran. How to Cite:  Muslim, B., Suryaningsih, S., Aprianti, R. F. (2020).  Analysis of Students' Creative Thinking Ability with Problems Solving in Terms of Adversity Quotient. TARBIYA: Journal of Education in Muslim Society, 7(2), 217-225. doi:10.15408/tjems.v7i2.15234.